2003
DOI: 10.1007/bf03006439
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fatty acid metabolism in taxan-induced myocardial damage with iodine-123 BMIPP SPECT: Comparative study with myocardial perfusion, left ventricular function, and histopathological findings

Abstract: Taxan impairs myocardial fatty acid metabolism. 123I-BMIPP myocardial SPECT is useful for evaluating the cardiotoxicity induced by taxan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…Novel SPECT techniques for early detection of cardiotoxicity are shown in Table 6. 46 These novel techniques include static volume indices and functional LV indices by gated SPECT ERNA and MPI, 27,28 sympathetic neuronal imaging with a wide variety of SPECT and PET tracers, [47][48][49][50][51][52][53][54][55] In-111 antimyosin which is a specific marker of myocyte injury and necrosis, 54,56,57 Tc-99m annexin V which visualized apoptosis and programmed cell death, [58][59][60] fatty acid scintigraphy which visualizes fatty acid retention in the lipid pool of the cytosol which can be impaired by cardiotoxic agents, 61 and direct imaging of In-111 trastuzumab to study trastuzumab targeting of the myocardium have been considered. 62 Each of these techniques would require a prospective clinical trial to assess its incremental value in avoiding clinical CHF.…”
Section: Novel Scintigraphic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel SPECT techniques for early detection of cardiotoxicity are shown in Table 6. 46 These novel techniques include static volume indices and functional LV indices by gated SPECT ERNA and MPI, 27,28 sympathetic neuronal imaging with a wide variety of SPECT and PET tracers, [47][48][49][50][51][52][53][54][55] In-111 antimyosin which is a specific marker of myocyte injury and necrosis, 54,56,57 Tc-99m annexin V which visualized apoptosis and programmed cell death, [58][59][60] fatty acid scintigraphy which visualizes fatty acid retention in the lipid pool of the cytosol which can be impaired by cardiotoxic agents, 61 and direct imaging of In-111 trastuzumab to study trastuzumab targeting of the myocardium have been considered. 62 Each of these techniques would require a prospective clinical trial to assess its incremental value in avoiding clinical CHF.…”
Section: Novel Scintigraphic Methodsmentioning
confidence: 99%
“…61 Taxanes in combination with carboplatin are reported to exert a more profound depression on myocardial FFA metabolism and myocardial contractile dysfunction than doxorubicin alone. The incremental value of reduced 123 I BMIPP or 123 I IPPA metabolism on prediction of chemotherapyinduced CHF remains undefined.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…They demonstrated that combination therapy with taxane and carboplatin did not affect myocardial perfusion but could impair fatty acid metabolism (109). A decrease of myocardial 123 I-BMIPP uptake took place in 56% of patients after treatment.…”
Section: Fatty Acid Usementioning
confidence: 99%
“…As a result, uptake of free fatty acids by the mitochondria may be reduced. This process can be reflected by 123 I-15-(piodophenyl)-3-(R,S)-methylpentadecanoic acid (BMIPP) scintigraphy or 123 I-paraphenyl pentadecanoic acid scintigraphy (106,109).…”
Section: Fatty Acid Usementioning
confidence: 99%
“…A study by Saito, et al, demonstrated early decreased uptake of 123 I-BMIPP in patients with preserved LV function after treatment with an anthracycline; similar decreases in 123 I-BMIPP uptake were observed in patients experiencing a decline in LVEF after receipt of a taxane and carboplatin (104,105). Recently, Carboni, et al, evaluated mitochondrial metabolism with 99m Tc-sestamibi (MIBI) in patients receiving multi-agent chemotherapy.…”
Section: Myocardial Metabolism Imagingmentioning
confidence: 80%